The impact of medical financial assistance on healthcare expenses and the medical financial burden: Evidence from rural China - Chen, Yucheng; Gao, Gongjing; Yuan, Fei; Zhao, Yuxiao (Frontiers in Public Health, 2023)
Background: Financial burden has become a key limitation to accessing health care in rural China as health care expenses continue to rise. To ensure that low-income people acquire basic health care services, China has implemented a medical financial assistance (MFA) policy to provide social health insurance and medical cash aid for the low-income people. Methods: Using data from the 2014 China Family Panel Studies (CFPS), we applied the propensity score matching (PSM) method to estimate the impact of MFA on health care expenses and the medical financial burden. Results: The empirical results show that the total annual health care expenditure of MFA beneficiaries is significantly higher than that of non-beneficiaries after matching. However, the ratio of out-of-pocket expenditure (OOPE) to per capita household non-food expenditure and the probability of catastrophic health care expenditure (CHE) of the low-income people do not decrease significantly after they are covered by MFA. Conclusion: MFA has reduced the inequality in health care utilization to a certain extent by improving access to health care for the low-income people. However, the medical financial burden of the low-income people is still heavy even when they are covered by MFA. Policy-makers should pay attention to raising the standards of MFA in rural areas and providing higher subsidies for the reasonable health care expenditure of the low-income people.